Sources of scientific bases of resource hike - Mikityuk S.A (Kharkov National Pedagogical University, 2010)
Topicality of the problems of the resource-based approach in personality development is substantiated in the article. The background to scientific foundations of this approach is progressive ideas of ancient scholars of Greece, China, India, who considered personality's inner processes. Subsequent researches were conducted by representatives of the economic science (economical resources, labour resources), which in their turn became prerequisites for psychologists and pedagogues to study these matters. Such concepts as resource-based approach, personality potential, and ability are studied.